2005
DOI: 10.1212/01.wnl.0000158654.07080.b0
|View full text |Cite
|
Sign up to set email alerts
|

EGFR tyrosine kinase domain mutations in human gliomas

Abstract: Gefitinib is an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor effective in patients with lung cancer with mutations in exons 19 and 21 of the EGFR tyrosine kinase domain. In this study, the authors tested the presence of such mutations in 95 gliomas including glioblastomas, anaplastic oligodendrogliomas, and low-grade gliomas. No mutation was found, which suggests that the biology of EGFR in gliomas is different from lung cancer and that this may be a factor in the resistance of glioblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 10 publications
3
42
0
5
Order By: Relevance
“…Interpretation of correlative studies linked to these trials (Table 2) have been limited by the low number of responders and by the different techniques used (24,30,32,33). Such studies confirmed previous reports suggesting that the EGFR tyrosine kinase domain mutations that predict response to EGFR TKI in lung cancer are absent in gliomas (34,35), including in those that allegedly responded to EGFR TKI. Most studies found no correlation between outcomes and EGFR overexpression or amplification (19,24,30,33), with the exception of one study that found that tumors with high levels of EGFR expression and low levels of phosphorylated AKT/protein kinase B (pAKT) were more likely to respond than those with low levels of EGFR expression and high levels of pAKT (32).…”
Section: Epidermal Growth Factor Receptorsupporting
confidence: 63%
“…Interpretation of correlative studies linked to these trials (Table 2) have been limited by the low number of responders and by the different techniques used (24,30,32,33). Such studies confirmed previous reports suggesting that the EGFR tyrosine kinase domain mutations that predict response to EGFR TKI in lung cancer are absent in gliomas (34,35), including in those that allegedly responded to EGFR TKI. Most studies found no correlation between outcomes and EGFR overexpression or amplification (19,24,30,33), with the exception of one study that found that tumors with high levels of EGFR expression and low levels of phosphorylated AKT/protein kinase B (pAKT) were more likely to respond than those with low levels of EGFR expression and high levels of pAKT (32).…”
Section: Epidermal Growth Factor Receptorsupporting
confidence: 63%
“…Although gliomas with EGFR amplification tended to respond more frequently than nonamplified tumors, this was not always the case. 27 Activating somatic mutations in the EGFR tyrosine kinase domain (exons 18-21), as found in gefitinib or erlotinib-sensitive nonsmall cell lung cancer, 34,35 appear to be a rare event in primary malignant gliomas 11,26,27,36,37 and were absent in our brain tumor xenograft models. Missense mutations in the extracellular domain of EGFR, as well as coexpression of EGFRvIII mutant and wild-type PTEN, are associated with a clinical and experimental response to anti-EGFR therapy in patients with glioblastoma and in glioblastoma cell lines.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, these mutations in the EGFR tyrosine kinase domain have not been found in patients with glioma (Barber et al, 2004;Rich et al, 2004a;Marie et al, 2005). Rich et al (2004a) showed that gefitinib-treated GBM patients with an event-free survival of more than 24 weeks did not harbour such EGFR point mutations .…”
Section: Discussionmentioning
confidence: 99%